Textual Economies and the Presentation of Statistical Material: Charts, Tables and Texts in 19th Century Public Education - Curtis, Bruce (Scientia Canadensis, 2006)
AbstractThis exploratory article develops the notion of textual economy, to investigate the place of statistical representations in practices of knowledge production. Nineteenth century Canadian state agencies generated massive quantities of statistical information. Yet, techniques of graphic representation were largely absent from official state papers and reports. The article investigates the discursive and textual strategies adopted by state servants to draw on statistical information in the absence of graphic representation.